Green corrosion inhibitors derived from plant extracts and drugs for mild steel in acid media: A review - Hency Thacker; Vijay Ram (Results in Surfaces and Interfaces)
Corrosion is defined as the process of degradation of the metal upon its chemical or electrochemical interaction with its surroundings. Such detroitation of metal is widely influenced its key factors like acids, alkalis, humidity, pH, temperature and salts that are responsible for the formation and succession of corrosion. Acids are widely employed in cleaning, descaling and pickling of metal surface. During this process, metallic parts undergo mass loss due to which corrosion is major industrial issue. Inorganic & organic substances, polymeric compounds, nanomaterials, plant extracts and drugs molecules have been employed as corrosion inhibitors to prevent corrosion of metals in acid media. The usage of plant extract as corrosion inhibitors is gaining familiarity nowadays due to its cost-effective, eco-friendly, plentiful availability and simplified production techniques. Different techniques used for the evaluation of corrosion inhibitors are mass loss measurements, potentiodynamic polarization & electrochemical impedance methods, density functional theory, molecular dynamic simulation and adsorption isotherm models.In the present review, various methods to prepare plant extracts along with their advantages and disadvantages are presented. Different plant extracts along with constituent molecules are presented so as to provide insight on their mechanism to prevent the corrosion of mild steel in acid media. The study also provides insight on the potential of drug molecules to prevent the corrosion of steel samples in acid media and their mechanism of action. The review concludes that plant extracts & drug molecules may serve as optimistic agents to prevent the corrosion of mild steel in acid media.